Negotiating success : - Hornickel, Jim (John Wiley and Sons, 2014)
How to execute win-win negotiations every time, in business and in life Negotiating Success provides expert guidance on how to improve strategies and outcomes in negotiating anything in professional and personal life. With a constant focus on the mind, body, and spirit of the professional negotiator, this easy-to- ready text brings a holistic approach to the hard and soft skills needed for ethical negotiations. The result is a better understanding of how to negotiate successfully for mutual benefit by all parties. Offers tips and tools, such as how to use positive psychology to unite your team, emotional intelligence for successful negotiation, and how to minimize conflict Spells out the six principles of ethical influence Written by Jim Hornickel, the founder of Bold New Directions, a transformational learning organization that provides training, coaching, retreats, and keynotes across the world, specializing in negotiation, leadership, communication, presentation, and corporate training Negotiating Success delivers an unparalleled blend of practical and explicit steps to take to achieve win-win negotiations, every time